On the Road Again: King David as Involuntary Migrant - Strine C. A. (De Gruyter, 2021)
When David ben Jesse’s triumphant return from battle in 1 Sam 18 causes King Saul to despise him, the wheels are set in motion to make David an asylum seeker, refugee, and return migrant. It is burdened with those traumatic experiences that he is announced king in 2 Sam 2. What follows is a narrative of familial conflict and fracture, involuntary migration for David again (2 Sam 15), and a final return (2 Sam 20). From this point, David lives a sedentary life. Although this is an atypical summary of the narrative in 1 Sam 18–2 Kings 2, it foregrounds the important role involuntary migration plays in its plot. This article will explore that story, looking especially at how David’s attitude toward mobility as king is implicitly rejected by the narrative.